1998
DOI: 10.1016/s0014-5793(98)00780-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a new class of scorpion toxins active against K+ channels

Abstract: cDNAs encoding novel long-chain scorpion toxins (64 amino acid residues, including only six cysteines) were isolated from cDNA libraries produced from the venom glands of the scorpions Androctonus australis from Old World and Tityus serrulatus from New World. The encoded peptides were very similar to a recently identified toxin from T. serrulatus, which is active against the voltage-sensitive`delayed-rectifier' potassium channel, but they were completely different from the long-chain and short-chain scorpion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 42 publications
1
55
0
3
Order By: Relevance
“…Of interest is clone 64 called here cTsTx-Kb (cDNA of TsTx-Kb), whose deduced amino acid sequence (Fig. 3) showed 64% identity with the long chain potassium ion channel blocker BmTxKb2 isolated from the scorpion Buthus martensii (Zhu et al, 1999), approximately 91% with the toxin TsTx-Kb described by Rogowski et al (1994) and its sequence is almost identical to the partial sequence of clones Ts-5 H Cl.14 and Ts-3 H Cl.3 published by Legros et al (1998). However, a deletion of a guanine base at Comparison of amino acid sequence of TbTx5 with TbTx IV-5 and TsTx.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Of interest is clone 64 called here cTsTx-Kb (cDNA of TsTx-Kb), whose deduced amino acid sequence (Fig. 3) showed 64% identity with the long chain potassium ion channel blocker BmTxKb2 isolated from the scorpion Buthus martensii (Zhu et al, 1999), approximately 91% with the toxin TsTx-Kb described by Rogowski et al (1994) and its sequence is almost identical to the partial sequence of clones Ts-5 H Cl.14 and Ts-3 H Cl.3 published by Legros et al (1998). However, a deletion of a guanine base at Comparison of amino acid sequence of TbTx5 with TbTx IV-5 and TsTx.…”
Section: Resultsmentioning
confidence: 92%
“…Finally, no significant similarity was found for some other isolated clones after DNA sequence analysis using GenBanK databases and the Fasta program of Pearson and Lipman (1988). In conclusion, we described the use of ELISA in the Comparison of amino acid sequence of cTsTxKb with BmTxKb2 (a putative potassium ion channel blocker from Buthus martensii, Zhu et al, 1999); TsTx-Kb (potassium ion channel blocker from Titus serrulatus, Rogowski et al, 1994) and clones Ts5 H Cl.14 and Ts3 H Cl.3 (Legros et al, 1998). Numbering corresponding to the signal peptide is negatively numbered.…”
Section: Resultsmentioning
confidence: 93%
“…The toxins in the same group share similar amino acid sequences and physiological or pharmacological functions. Though over 40 different scorpion K + channel toxins have been reported [22], there has been little information on their gene structures. Only the genes of KTX from Androctonus australis [14], ChTX from Leiurus quinquestriatus hebraeus [16] and toxin Ts κ from Tityus serrulatus (only the cDNA sequence is available) [15] have been elucidated.…”
Section: Figure 3 Genomic Dna Sequence and Deduced Amino Acid Sequencmentioning
confidence: 99%
“…A multiple sequence alignment made by using CLUSTAL revealed that these new toxins are related to the insect defensins. Their precursors contain a prosequence of eight residues (8,13).…”
Section: Cdna Sequence Of Bmtxks2mentioning
confidence: 99%